Labor Market Institutions and the Employment-Productivity Trade-Off : A Wage Posting Approach - Arnaud Chéron; Jean-Olivier Hairault; François Langot (Institute for the Study of Labor (IZA), 2004)
This paper analyzes the implications of labor market institutions and policies on the employment-labor productivity trade-off. We consider an equilibrium search model with wage posting and specific human capital investment where unemployment and the distribution of both wages and productivity are endogenous. By means of simulations of this model estimated on French data, we show that the minimum wage allows a high production level to be reached by inducing increased training investment, even if its optimal level is weaker. Considering the payroll tax subsidies implemented to lower the labor cost without removing the minimum wage legislation, we show that this policy has been welfare improving, and has been relatively well managed by spreading subsidies over a large range of wages, and not only at the minimum wage level.
Keywords: C51; J38; J31; J24; 330; employment; productivity; wage posting; labor costs; Arbeitsmarktflexibilisierung; Beschäftigung; Produktivität; Arbeitsuche; Lohnbildung; Bildungsinvestition; Mindestlohn; Arbeitsproduktivität; Schätzung; Frankreich